The Formative Assessment Handbook Resources to Improve Learning Outcomes for All Students - Freibrun, Marine; Brunet, Sandra (Jossey-Bass, 2024)
The Formative Assessment Handbook addresses topics in the area of formative assessment in the K-12 classroom. The first part of the book addresses what formative assessment is, what it looks like, and why it is important in the classroom. The second part of the book is filled with ready-to-go activities & reproducibles that educators can utilize in their classroom immediately. This includes routines for pre-, during, and post- lesson, writing and reflecting, visuals, and collaborative routines. These two parts of the book provide both an overview of formative assessment, as well as a "how-to" guide on implementation.